The Relationship between Assertive Behavior and the Tendency to Become the Object of Bullying in New Students - Bahrun, Muh.Yasin Ansari; Dewi, Eva Meizara Puspita; Djalal, Novita Maulidya (Polteknik Ilmu Pemasyarakatan, 2023)
Bullying is one of the problems among freshmen who often lack direct, honest, and assertive self-expression to defend personal rights in expressing feelings, also called assertive behavior. This study aims to look at the relationship between assertive behavior and the tendency to be the object of bullying in freshmen. This study uses a quantitative approach with descriptive analysis methods, hypothesis testing (spearman's rho), and t-test (mann-whitney). The subjects of this study were 320 new students of the Faculty of Engineering, Makassar State University. The results showed that there is a relationship between assertive behavior and the tendency to be the object of bullying in new students (p = 0.000, r = 0.312). This means that the higher the assertive behavior, the lower the tendency to be the object of bullying in new students and vice versa. The results of additional analysis show that there are no differences in assertive behavior, however, there are differences in the tendency to be the object of bullying based on gender. It can be concluded that there is a relationship between assertive behavior and the tendency to be the object of bullying in freshmen with a moderate correlation.